2017
DOI: 10.1080/15548627.2017.1325062
|View full text |Cite|
|
Sign up to set email alerts
|

Exercise reestablishes autophagic flux and mitochondrial quality control in heart failure

Abstract: We previously reported that facilitating the clearance of damaged mitochondria through macroautophagy/autophagy protects against acute myocardial infarction. Here we characterize the impact of exercise, a safe strategy against cardiovascular disease, on cardiac autophagy and its contribution to mitochondrial quality control, bioenergetics and oxidative damage in a post-myocardial infarction-induced heart failure animal model. We found that failing hearts displayed reduced autophagic flux depicted by accumulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
96
1
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(109 citation statements)
references
References 53 publications
6
96
1
6
Order By: Relevance
“…Considering that autophagy is impaired in neurogenic myopathy, we next set out to determine whether the re-establishment of autophagic flux is sufficient to improve skeletal muscle proteostasis and counteract SNC-induced skeletal muscle damage. We have recently demonstrated that exercise training is able to restore the autophagic flux in failing hearts contributing to better disease prognosis 21 . To evaluate the effects of exercise training in autophagy in a model of neurogenic myopathy, rats were submitted to 4 weeks of moderate running training on a treadmill prior to SNC surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Considering that autophagy is impaired in neurogenic myopathy, we next set out to determine whether the re-establishment of autophagic flux is sufficient to improve skeletal muscle proteostasis and counteract SNC-induced skeletal muscle damage. We have recently demonstrated that exercise training is able to restore the autophagic flux in failing hearts contributing to better disease prognosis 21 . To evaluate the effects of exercise training in autophagy in a model of neurogenic myopathy, rats were submitted to 4 weeks of moderate running training on a treadmill prior to SNC surgery.…”
Section: Resultsmentioning
confidence: 99%
“…Further, Bhuiyan et al [173] reported that voluntary wheel-running for 7 months increased cardiac autophagy and attenuated myocardial dysfunction as indicated by conserved left ventricular function in mice with desmin-related cardiomyopathy. Similarly, exercise training re-established autophagic flux and mitochondrial quality control in failing rat hearts subsequent to myocardial infarction [174]. Likewise, exercise training induced changes in autophagic function and fatty acid utilization in rabbit hearts following MI [175].…”
Section: Exercisementioning
confidence: 92%
“…Aerobic exercise could change mitochondrial phenotype, such as upregulating antiapoptotic protein (MCL-1 and BLC-2) and reducing proapoptotic proteins [70,176]. Also, physical exercise could regulate fusion (such as MFN1/2 and OPA1) and fission [177][178][179][180] and enhance mitochondrial biosynthesis to promote mitochondrial dynamics [181]. The number of autophagic vacuoles increased in neurons in the brain regions of PD patients.…”
Section: Physical Exercise Can Enhance Mitochondrial Functionmentioning
confidence: 99%